(untitled) (Comparatismi, 2025)
Building on the concept of performativity as developed by J. L. Austin and the critical and social reinterpretation of this concept by Judith Butler, gender can be viewed as a construct formed and reinforced through the act of expression. Based on this idea, this article analyses performativity as a useful interpretative tool for understanding literary genre dynamics, challenging essentialist ideas to emphasise the pragmatic-relational dimension of genre. To illustrate this, two recent literary phenomena will be considered: the New Weird and climate fiction.